Pro-oxidative processes and cytokine response to training in professional basketball players - Zembron-Lacny, A.; Slowinska-Lisowska, M.; Superlak, E. (Journal of Human Kinetics, 2008)
In the present study, we evaluated the plasma concentration of inflammatory mediators including cytokines and their relation with oxidative damage markers in training cycles of basketball players. Sixteen professional players of the Polish Basketball Extraleague participated in the study. The basketball players were observed during the preparatory period and the play-off round. Twenty healthy and untrained males composed of the reference group. The comparative study has shown significantly higher levels of lipid peroxidation (TBARS) and protein carbonylation (PC) in nonathletes than in basketball players during the observed training periods. Tumour necrosis factor ƒ¿ (TNFƒ¿), similarly to TBARS and PC, was significantly higher in nonathletes than athletes, except at the end of the play-off round. Interleukin-6 (IL-6) was lower in nonathletes than athletes in the preparatory period but it was higher in athletes in play-off round. In basketball players, the high level of IL-6 directly correlated with TBARS (r = 0.763, p<0.001) and PC (r = 0.636, p<0.001) during the preparatory period, whereas the high level of TNFƒ¿ inversely correlated with TBARS (r = -0.601, p<0.001) and PC (r = -0.650, p<0.001) in the play-off round. The activity of creatine kinase (CK) was significantly increased during the training mezocycles in basketball players compared with nonathletes, and reached the highest activity at the end of the play-off round. CK activity did not correlate with oxidative damage markers and cytokines in both untrained and trained subjects. results have shown the reduction in oxidative damage and improvement in cytokine response following professional training, as well as the relationship between inflammatory and pro-oxidative processes in basketball players.